Interaction of Cysteine with Aun (n=8, 10, 12) Even Neutral Clusters: A Theoretical Study. Issue 9 (28th March 2017) - Srivastava, Ruby
Abstract: The intermolecular interactions between gold nanoparticles Aun (n=8, 10, 12) with (neutral (o), cationic (+) and anionic (‐)) cysteine amino acid is investigated by means of density functional theory DFT –B3LYP/LANL2DZ:6‐31+G** mixed basis sets. The studies have been carried out on the structural, electronic and bonding properties of the major bonding factors: (a) the anchoring S−Au, O−Au and N−Au and (b) non‐conventional N–H⋅⋅⋅Au, O–H⋅⋅⋅Au bonds. Bader topological AIM analysis was carried out to interpret the nature of bonds to the complexation behavior. The NBO and frontier molecular orbital analysis indicated that the lone pair electrons of nitrogen, oxygen and sulphur atoms are transferred to the antibonding orbitals of gold for the complex with anchoring bonds, while the lone pair electrons of gold are transferred to the antibonding orbitals of O−H⋅⋅⋅Au bonds. Our results demonstrated that cysteine‐Aun form stable complexes. Among the three (neutral, cationic and anionic) forms of cysteine, cationic cysteine complexes interact more stronger with the gold metal clusters. The bonding strength between gold clusters and cysteine is positively correlated with the S–Au overlap‐weighted bond order and negatively correlated to the S–Au bond length. Abstract : The intermolecular interactions between gold nanoparticles Aun (n=8, 10, 12) with (neutral, cationic and anionic) cysteine amino acid is investigated by means of density functional theory. The structural, electronic and bonding properties of the anchoring and non‐conventional bonds are analyzed. Our results demonstrated that cysteine‐Aun form stable complexes and the interaction of cationic cysteine complexes are more stronger with the gold metal clusters. The NBO and frontier molecular orbital analysis and AIM analysis was carried out to interpret the nature of bonds to the complexation behavior. The correlation of bonding strength and S–Au overlap‐weighted bond order between gold clusters and cysteine is also discussed.